Analisis dan Perancangan Sistem Informasi Reservasi Prasarana Olahraga pada Dinas Kepemudaan dan Olahraga Provinsi Jambi - Lubis, Hariyati; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2021)
Dinas Kepemudaan dan Olahraga Provinsi Jambi does its sport facilities reservation business process conventionally. To know the availability of a certain sport facilities to be reserved, people have to submit a letter to this institution and wait for the response letter. Sport facilities reserved are recorded manually in a ledger, which is at the risk of being damaged or being lost, and mistake at recording the reservation can results in overlapping reservation schedule. Sport Facilities Reservation Information System at Dinas Kepemudaan dan Olahraga Provinsi Jambi is designed to make reservation process easy for both public and the institution. This system is designed by using object oriented modeling in the form of use case diagram, activity diagram, and class diagram. The output of this research is a prototype of Sport Facilities Reservation Information System at Dinas Kepemudaan dan Olahraga Provinsi Jambi.